Building specialized dictionaries using lexical functions - Dancette, Jeanne; L’Homme, Marie-Claude (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
It is now widely acknowledged that terms enter into a variety of structures and that classic taxonomies and meronymies represent only a small part of the relationships terms share. This can be seen in recent specialized dictionaries that account for derivational relationships, co-occurrents, synonyms, antonyms, etc. It also has been underlined in several articles written by terminologists as well as linguists or computational scientists working with specialized corpora. This article will discuss the advanta ges and shortcomings of trying to account for semantic relations between terms using a specific framework, i.e. lexical functions (Mel’cuk et al. 1984-1999, 1995). It is based on a long-term project aimed at converting an existing paper dictionary (Dancette & Réthoré 2000) into a relational database. We will show that even if lexical functions have several advantages, a number of decisions must be made to accommodate the description of specialized terms.